Development of a compact explicit algebraic model for the turbulent heat fluxes and its application in heated rotating flows. (July 2015) - Müller, H.; Younis, B.A.; Weigand, B.
Abstract: The paper describes the development of a compact, non-linear model for the turbulent heat fluxes, and its application to heated flow in a rotating channel. The model was formulated by expanding the tensorial functional of dependent variables, and by applying certain simplifications to obtain an algebraic and explicit model that contains direct dependence on the rotational body forces, and on the gradients of mean velocity. The model was implemented into OpenFOAM, the open-source flow solver, and its performance was assessed in stationary wall-bounded and free heated flows, and in a heated channel with spanwise rotation. Comparisons with experimental data and with results from Direct Numerical Simulations show that the new model performs better than alternative closures.